ETIKA POLITIK ARISTOTELES DAN RELEVANSINYA BAGI KEMAJEMUKAN RELIGIUS DI INDONESIA - Anto, Puji (UIN Sunan Kalijaga Yogyakarta, 2022)
Aristotle's political philosophy is very important and relevant to discuss today, because it was the foundation of modern political theory. Aristotle provided the concept of the state with the best possibilities in reality, not on the basis of an abstract ideal order. From his studies Aristotle concluded that the most practicable state system is a constitutional government with the active participation of its citizens, or what he termed